Spectrophotometric, chemometric and chromatographic determination of naphazoline hydrochloride and chlorpheniramine maleate in the presence of naphazoline hydrochloride alkaline degradation product - Nour el deen Sayed; Maha Hegazy; Mohammed Abdelkawy; Rehab Abdelfatah (Faculty of Pharmacy, Cairo University, 2013)
Four accurate and sensitive methods were developed and validated for determination of naphazoline hydrochloride (NAP) and chlorpheniramine maleate (CLO) in the presence of naphazoline hydrochloride alkaline degradation product (NAP Deg). The first method is a spectrophotometric one , where NAP was determined by the fourth derivative (D4) spectrophotometric method by measuring the peak amplitude at 302 nm, while CLO was determined by the second derivative of the ratio spectra (DD2) spectrophotometric method at 276.4 nm. The second method is a chemometric-assisted spectrophotometric method in which partial least squares (PLS-1) and partial component regression (PCR) were used for the determination of NAP, CLO and NAP Deg using the information contained in their absorption spectra of ternary mixture. The third method is a TLC-densitometric one where NAP, CLO and NAP Deg were separated using HPTLC silica gel F254 plates using ethyl acetate:methanol:ammonia: (8:2:0.5, by volume) as the developing system followed by densitometric measurement at 245 nm. The fourth method is HPLC method where NAP, CLO and NAP Deg were separated using ODS C18 column and a mobile phase consisting of 0.1 M KH2PO4 (pH = 7):methanol (55:45 v/v) delivered at 1.5 mL min−1 followed by UV detection at 265 nm. The proposed methods have been successfully applied to the analysis of NAP and CLO in pharmaceutical formulations without interference from the dosage form additives and the results were statistically compared with a reported method.